The Service of the Mashpee Indians in the American Revolution. - Denney, Jacob Thomas. (Tufts University. Tisch Library., 2005)
Tisch Library Undergraduate Research Award Winner, 2012. During the American Revolution, twenty-nine Mashpee Indians served in the Continental Army. Only two of those confirmed twenty-nine enlisted men survived the war to file a pension application; a dramatic loss for a community with less than sixty male heads of household in 1776. The death toll was possibly so high because these Mashpee soldiers served enlistments substantially longer than the average Continental Army soldier, even in the face of increasing barriers to service for non-white soldiers. Those Mashpee who enlisted were not primarily motivated by economic necessity, but were largely bound to the liberal ideology of the revolution and fought to gain political agency in a society that had largely ignored or oppressed them. However, in spite of their contribution to the rebel cause, like many Indian tribes they found themselves disenfranchised by its outcome.